1996
DOI: 10.1021/ed073p82
|View full text |Cite
|
Sign up to set email alerts
|

The Complexometric Determination of Calcium and Magnesium in Limestone Using a Laser Photometer for Endpoint Identification

Abstract: An alteration of the classic complexometric titration of calcium and magnesium with EDTA was made to incorporate a laser photometer for endpoint detection. The photometer utilized a He-Ne laser, which allowed the red to blue transition of the calgamite indicator to be followed by monitoring the change in beam absorbance. A photodiode and an inexpensive computer interface were used to record the intensity of the transmitted laser beam as a function of time. This method makes the experiment much more accessible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The students practice data acquisition as part of another online lesson at home and calibrate (against an alcohol thermometer) the response of a thermistor to a cup of hot water as it cools. In the subsequent lab period students acquire data from a Spectronic 20 and then their own colorimeter (Figure ) based on an LED as a light source and a photodiode as a detector. Later classes cover the principles of common light detectors and operational amplifiers.…”
Section: Introducing Microcontrollers Into the Instrumental Analysis ...mentioning
confidence: 99%
“…The students practice data acquisition as part of another online lesson at home and calibrate (against an alcohol thermometer) the response of a thermistor to a cup of hot water as it cools. In the subsequent lab period students acquire data from a Spectronic 20 and then their own colorimeter (Figure ) based on an LED as a light source and a photodiode as a detector. Later classes cover the principles of common light detectors and operational amplifiers.…”
Section: Introducing Microcontrollers Into the Instrumental Analysis ...mentioning
confidence: 99%
“…These chelates are known and have been used in volumetric analysis , for a long time. They are being used for the quantitative determination of more than 45 elements by direct and back-titration procedures to obtain a visual end point , or by use of various techniques such as pH metry, spectrophotometry, capillary electrophoresis, high performance liquid chromatography, and ion chromatography . However, the exact use of these reagents for quantitative determination of lanthanides using a conductometric technique is still not known.…”
Section: Introductionmentioning
confidence: 99%
“…The Web site for the cleaner confirmed that it contains EDTA along with isopropanol, surfactant, and fragrance (2). Several articles in this Journal and in textbooks provide additional information about chelating agents and complexometric titrations (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%